2010
DOI: 10.1128/aem.00896-10
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of Thermobifida fusca Cutinase-Carbohydrate-Binding Module Fusion Proteins and Their Potential Application in Bioscouring

Abstract: Cutinase from Thermobifida fusca is thermally stable and has potential application in the bioscouring of cotton in the textile industry. In the present study, the carbohydrate-binding modules (CBMs) from T. fusca cellulase Cel6A (CBM Cel6A ) and Cellulomonas fimi cellulase CenA (CBM CenA ) were fused, separately, to the carboxyl terminus of T. fusca cutinase. Both fusion enzymes, cutinase-CBM Cel6A and cutinase-CBM CenA , were expressed in Escherichia coli and purified to homogeneity. Enzyme characterization s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…CBM6 was fused to the C -terminus of Cel5A_2R2 using 3-step overlap PCR [19]. The construction procedure is shown in Figure S1.…”
Section: Methodsmentioning
confidence: 99%
“…CBM6 was fused to the C -terminus of Cel5A_2R2 using 3-step overlap PCR [19]. The construction procedure is shown in Figure S1.…”
Section: Methodsmentioning
confidence: 99%
“…In the presence of pectinase, binding activity of the Thermobifida fusca cellulase and Cellulomonas fimi carbohydrate binding domain fusions with the cutinase was 40 and 45 % higher than that of the native enzyme, respectively. In addition, a far higher amount, up to 3-fold higher than with native cutinase, of released fatty acids were obtained with the fusion proteins (Zhang et al 2010).…”
Section: Use Of Cutinases In Textile Processingmentioning
confidence: 98%
“…The pH stability was highest for the three chimeric enzymes after incubation for 24 hrs at 37ºC under optimum pH (Zhang et al 2010). Figure 4 shows the activities of CUT-N1 at optimum pH and after incubation at temperatures of 30 to 70ºC during 30, 60 and 90 min.…”
Section: Ultrafiltration Of Metabolic Liquidmentioning
confidence: 99%
“…Zhang et al (2010) determined optimal temperature of 50ºC for recombinant cutinases and observed the half-life of 53 hrs after incubation at optimum temperature. Ronkvist et al (2009) characterized cutinases produced by different microorganisms and determined thermostability at 50ºC for cutinases produced by Pseudomonas mendocina and F. solani, while cutinases from Humilica insolens showed thermostability at 70-80ºC.…”
Section: Thermal Stability Of Cutinasesmentioning
confidence: 99%